Implementation Of Good Governance Principles In Public Service Reform: Challenges, Adaptive Strategies, and Impacts - Imran Al ucok Nasution; Marihot Manullang (International Journal of Management and Business Economics, 2026)
Good principle governance Good governance is a key agenda in the transformation of contemporary public administration in Indonesia. Along with the dynamics of regional autonomy and demands for open information, the integration of the values of accountability, transparency, and participation has become a central instrument for eroding classic bureaucratic pathologies such as inefficiency, corruption, and low responsiveness. This article aims to analyze in depth the developments, systemic obstacles, acceleration strategies, and the real impact of the institutionalization of the principles of good governance. governance on the quality of public services. Using a qualitative-descriptive approach with literature studies and regulatory reviews, this analysis found that the realization of ideal governance is often hampered by cultural resistance from officials, limited infrastructure, and suboptimal leadership commitment at the local level. However, the integration of clean governance has consistently been shown to significantly increase public trust and budget efficiency. An adaptive framework, transformative leadership, and strengthened community-based oversight are needed to realize an inclusive, accountable, and public-benefit-oriented government